A Comparison Between Analytical Solutions for Lightning-Induced Voltages Calculation - Andreotti, A.; Assante, D.; Pierno, A.; Rakov, V. A.; Rizzo, R. (Elektronika ir Elektrotechnika, 2014)
An exact closed form solution for the calculation of lightning-induced voltages on overhead lines has been recently proposed by A. Andreotti et al. (2012). Predictions of this exact formulation are compared here to those based on approximate analytical solutions proposed in the literature. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.2967